Implementation Comic Life Learning Media for Class VII to Improve Students’ Mathematical Communication and Mathematical Disposition Ability - Anggie Munthia Safitri; Euis Eti Rohaeti; Wahyu Hidayat ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
The purpose of this research is to see how effective the learning media that have been designed are. The method used in this research stage is development research, in which learning media based on the Comic Life assisted set materials are developed.  This Study included 54 students from Bandung and 114 students from Ngamprah Subdistrict from the Junior High School association VII grade level. In the development of media, there are four stages of research namely define; design; develop; disseminate. The stage result in an average data validation of the material expert of 76.3% for the first stage and 80.8%% for the second stage. Stage I validation findings were 53.3%, stage II validation was 74%, and stage III validation was 81%. Student replies of 76% and instructor responses of 78% revealed the findings of the validation in limited trials and broad trials. Meanwhile, 79.5% of student responded positively during product testing. The level of efficacy of learning media utilizing Comic Life is attained with an N-Gain of 0.34, implying that the level of effectiveness of Comic Life assisted learning is quite effective. According to the findings of the mathematical communication and disposition exam, students who study using the Problem Based Learning approach with Comic Life have a better-mathematical abilities than those who learn conventional learning. In terms of mathematical disposition, it can be determined that students who utilize the Comic Life assisted Problem Based Learning technique have a better mathematical disposition than those use conventional learning. This development research is based on the learning design produced and the characteristics of students.